Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Teams Games Tournament dan Model Pembelajaran Ekspositori terhadap Hasil Belajar Pendidikan Kewarganegaraan - Wahyu Dwi Setiawan; Al. Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: This study aims to determine the differences learning outcome of Civics Subject between Teams Games Tournament learning model classes with expository learning model classes. The study results indicate that learning outcome of Civics Subject are taught by using Teams Games Tournament learning model trend higher while those are taught by using expository learning model trend lower. The Z test results obtained Zc = 2,02338385 and Zt= 1,645. From the Z test results, can be concluded that Zc> Zt, means there are differences in learning outcome of Civics Subject between Teams Games Tournament learning model classes with expository learning model classes. Based on Z test results, can be concluded that Teams Games Tournament learning model is more influence than expository learning model on the learning outcome of Civics Subject.